2016
DOI: 10.1371/journal.pone.0146599
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in Children Hospitalized with Respiratory Syncytial Virus Infection

Abstract: BackgroundThe risk of bacteremia is considered low in children with acute bronchiolitis. However the rate of occult bacteremia in infants with RSV infection is not well established. The aim was to determine the actual rate and predictive factors of bacteremia in children admitted to hospital due to confirmed RSV acute respiratory illness (ARI), using both conventional culture and molecular techniques.MethodsA prospective multicenter study (GENDRES-network) was conducted between 2011–2013 in children under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
1
24
0
2
Order By: Relevance
“…Streptococcus pneumoniae (pneumococcus) and respiratory syncytial virus (RSV) are the leading causes of lower respiratory tract infections (LRTIs) amongst children and older adults (1,2). Importantly, co-infections with these pathogens are becoming increasingly recognized as a major contributor to severe LRTIs requiring hospitalizations (3,4). Innate responses to RSV or pneumococcal bacteria can prime the host for secondary infection by activating inflammatory cells such as macrophages and neutrophils (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae (pneumococcus) and respiratory syncytial virus (RSV) are the leading causes of lower respiratory tract infections (LRTIs) amongst children and older adults (1,2). Importantly, co-infections with these pathogens are becoming increasingly recognized as a major contributor to severe LRTIs requiring hospitalizations (3,4). Innate responses to RSV or pneumococcal bacteria can prime the host for secondary infection by activating inflammatory cells such as macrophages and neutrophils (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and epidemiologic data suggest that RSV is linked to increases in the frequency ( 5 ) and severity ( 6 ) of pneumococcal disease. It was also demonstrated that mice infected with RSV before pneumococcal challenge as well as mice infected with both respiratory pathogens simultaneously showed enhanced lung alterations and elevated levels of bacteremia ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several predictive models had reports consistently the chest indrawing as predictive of prolonged LOS that is which is biologically plausible and expected due that this sign also is a universal marker of severity of the disease, as well as the presence of underlying conditions (congenital heart disease, chronic lung conditions, immunocompromised states) (3,(6)(7)(8)(20)(21)(22) or C-reactive protein (CRP) as a biomarker of severity and bacterial co-infection in patients hospitalized for bronchiolitis (23)(24)(25) Our study has limitations. First, since this study was based on medical records review, we cannot include other variables such as environmental pollution and genetic factors, and residual confounding cannot be excluded.…”
Section: Discussionmentioning
confidence: 96%